Hours of occurrence of daily extreme air temperature and relative humidity in Santa Maria, RS (Agrometeoros, 2020)
This study aimed to determine the most frequent occurrence times of daily extremes of air temperature and relative humidity in Santa Maria, RS, Brazil. Hourly data from 2002 to 2019 were obtained from an automatic weather station belonging to INMET. The relative frequencies of the times of occurrence of the daily minimum and maximum air temperatures were calculated for each month. The results allowed knowing the times of occurrence of the daily maximum and minimum air temperatures and relative humidity in Santa Maria, RS, Brazil. Thus, it is possible to obtain greater accuracy in the estimation of chill hours, duration of vernalization periods, and in the quantification of stresses caused by inadequate values of these variables in agriculture. The daily minimum air temperature is most frequently recorded at 7:00 a.m., varying from 6:00 a.m. to 8:00 a.m. throughout the year. The daily maximum air temperature occurs most frequently at 4:00 p.m., while in December and January, it is delayed to 5:00 p.m. The daily maximum relative air humidity occurs most frequently at 7:00 a.m., varying from 7:00 a.m. to 9:00 a.m. throughout the year. The daily minimum relative air humidity, on the other hand, occurs most frequently at 5:00 p.m., varying from 4:00 p.m. to 6:00 p.m. in the different months of the year.